Increment coring induced traumatic resin ducts in white spruce but not in lodgepole pine - Klutsch, Jennifer G. (2020)
Injury from sampling increment cores may induce defense responses in trees, which may vary between species and reflect differing defense allocation strategies against attack by insects and pathogens. We recorded presence of systemic induction of traumatic resin ducts from early-season increment coring in mature white spruce (Picea glauca) and lodgepole pine (Pinus contorta var. latifolia) trees. In the year of coring, traumatic resin ducts formed three months later, 20 cm below the initial coring site in the xylem of white spruce and showed little variation in response among the spruce families. In contrast, lodgepole pine did not form traumatic resin ducts in trees cored earlier in the growing season. Although traumatic resin ducts are induced by biotic and abiotic disturbances, we found a species-specific defense response to increment coring in two ommon boreal forest tree species.